PERSEPSI KONSUMEN DAN TINGKAT MINAT BELI TERHADAP SIRUP CASCARA CASANDRA BRAND NETISANE: ANALISIS BERDASARKAN PENGEMBANGAN MODEL PLANNED BEHAVIOR - Hapsari, Hepi; Esla Karimah, Bella; Eti Suminartika (Fakultas Pertanian Universitas Janabadra, 2025)
The development of the innovative beverage industry encourages the creation of environmentally friendly products, one of which is cascara casandra syrup from Brand Netisane, which processes coffee skin waste into a useful product that is low in caffeine and high in antioxidants. Despite its great potential, consumer awareness of the advantages of this product is still low. This study aims to examine consumer perceptions and the level of purchase intention towards cascara casandra syrup from Brand Netisane. The variables used in this study include attitudes, subjective norms, perceived behavioral control, environmental concerns, and health awareness. With a quantitative descriptive approach, this study used the census method with all product consumers as respondents. A total of 40 respondents participated in this study, and data were collected through a Likert scale questionnaire distributed online through Goofle Form. The results showed that the purchase interest in cascara syrup reached 82%. Positive perceptions are reflected in attitudes (82.17%), subjective norms (65.5%), perceived behavioral control (85.33%), environmental concerns (84%), and health awareness (82.75%). The main factor influencing purchase intention is health benefits which reached 84.5%.